Efectos del bio-sol en la producción de abono orgánico líquido tipo biol obtenido bajo diferentes niveles de estiércol de ganado - Pacheco González, Angela Diana (2007)
In the cooperative January 27, located in the canton Santa Rosa four treatments were compared in three dates to obtain biol. The objectives were: 1. to compare three dose of livestock manure and one of rumen in the process of biol elaboration (payments fermented liquid). 2. to Analyze the costs of production of the bioles. A design of Complete Blocks was used at random with 4 treatments: three dose of bovine manure (40, 30 and 20 kg), and 30 kg of rumen, and three repetitions that were the dates. Of the obtained results, and after the respective discussion, you concluded: 1. the best treatments in production of liters of biol corresponded to the smallest dose of manure and the treatment with rumen. 2. It was inversely proportional the production in liters of biol for the dosages of the manure. To more dose smaller production, and vice versa. 3. The first date was the one that better he/she surrendered in liters of biol that the other two dates. 4. The rumen in the first date had better nitrogen concentrations and match. 5. The temperatures to crop went superior and different to the temperatures to the beginning. 6. The temperatures to the beginning didn't have any relationship with the production in liters, neither the temperatures to the crop. 7. The best treatments in net revenues and in relationship beneficio/costo they were the treatments 20 kg of bovine manure and the Rumen. The process of obtaining the bioles was positive since all the treatments had positive net revenues with index bigger beneficio/costo that 1. The realization of other experimental works was recommended but with products obtained in the same place.